Recognizing Africa's forgotten citizens: the rural poor - Sinkam, Nana (Technical Centre for Agricultural and Rural Cooperation, 1994)
Professor Nana Sinkam is Director of the Joint Agricultural Division of the Economic Commission for Africa and the UN Food and Agriculture Organization. Africa is a major recipient of foreign aid for rural development and has become highly dependent...